Penalaran Fikih Peserta Didik Melalui Asesmen Berbasis Kasus pada Materi Sedekah, Hibah, dan Hadiah di MTs Al Huda Kedungwaru Tulungagung - Sofiana Sholikah (Social Science Academic, 2026)
Jurisprudence learning assessments in madrasas are still dominated by measuring conceptual mastery, thus failing to map students' reasoning abilities in solving contextual problems. This study aims to describe the profile of students' fiqh reasoning through a case-based assessment on the material of alms, grants, and gifts and to describe students' responses to the application of the assessment. The study used a quantitative approach with a descriptive type. The research subjects were 14 eighth-grade students of MTs Al Huda Kedungwaru Tulungagung who were selected using a total sampling technique. Data were collected through a case-based assessment compiled based on five indicators of fiqh reasoning, namely identifying problems, analyzing cases, determining law, providing legal arguments, and drawing conclusions, as well as student response questionnaires. The instrument's content validity was analyzed using Aiken's V coefficient, while the data were analyzed descriptively using scores and percentages. The results showed that 57.14% of students were in the high reasoning category, 35.71% were in the very high category, and 7.14% were in the moderate category. All reasoning indicators scored high with an average score of 85.00%, while the determining law indicator achieved the highest percentage (89.29%). Student responses to the case-based assessment were very positive, with an average score of 85.18%. These findings indicate that the case-based assessment comprehensively maps Islamic jurisprudence reasoning skills and is highly accepted by students.